2017
DOI: 10.1210/js.2017-00439
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Exposure to Dexamethasone Affects Nonneuronal Cells in the Adult Paraventricular Nucleus of the Hypothalamus

Abstract: Neurons in the paraventricular nucleus of the hypothalamus (PVN) integrate peripheral signals and coordinate responses that maintain numerous homeostatic functions. An excess of glucocorticoids during fetal development results in long-lasting consequences tied to disrupted PVN development. The PVN contains a distinct neuronal population and a threefold greater vascular density than the surrounding brain regions that prepubertally is reduced in offspring exposed to excess glucocorticoids in utero. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Further, the strongest GxS interaction was detected for SCZ in the 5' UTR of MOCOS (rs11665282; p=1.48×10 −7 ), which, based on evaluation of brain expression datasets, is highly expressed in endothelial cells lining blood vessels (Supplementary Figure 24). Interestingly, our previous work on sex differences in the positioning of cells containing ERα in the PVN associated with impaired GABA-B signaling (65) also was significantly associated with sex differences in vascular development, being more severe in females and associated with depression-related behaviors (94). These previous studies suggest potentially shared genetic risks across these disorders with vascular dysfunctions and may explain high comorbidity of disorders like MDD and SCZ with CVD (90).…”
Section: Several Mechanisms Could Account For Opposite Direction Intementioning
confidence: 74%
See 1 more Smart Citation
“…Further, the strongest GxS interaction was detected for SCZ in the 5' UTR of MOCOS (rs11665282; p=1.48×10 −7 ), which, based on evaluation of brain expression datasets, is highly expressed in endothelial cells lining blood vessels (Supplementary Figure 24). Interestingly, our previous work on sex differences in the positioning of cells containing ERα in the PVN associated with impaired GABA-B signaling (65) also was significantly associated with sex differences in vascular development, being more severe in females and associated with depression-related behaviors (94). These previous studies suggest potentially shared genetic risks across these disorders with vascular dysfunctions and may explain high comorbidity of disorders like MDD and SCZ with CVD (90).…”
Section: Several Mechanisms Could Account For Opposite Direction Intementioning
confidence: 74%
“…Further, the strongest GxS interaction was detected for SCZ in a locus in the MOCOS gene most highly expressed in endothelial cells lining blood vessels. Interestingly, our previous work on sex differences in neuronal migration due to impaired GABA-B signaling (62) was also significantly associated with sex differences in hypothalamic neurovascular development, being more severe in females and associated with depression-related behaviors (85). In fact, a recent meta-analysis of 22 available gene expression microarrays across multiple organs and tissues cited areas of the brain (i.e., anterior cingulate cortex, implicated in MDD, SCZ and BIP) with the most substantial sex differences in gene expression, followed by the heart (86).…”
Section: Discussionmentioning
confidence: 92%
“…Further supporting the sensitivity of astrocytes to ELA, there have been several reports on the effect of other forms of early stress on the astrocytic population, including dexamethasone exposure (Claessens et al, ; Frahm, Handa, & Tobet, ; McArthur, Pienaar, Siddiqi, & Gillies, ), early‐life exposure to noise (Jauregui‐Huerta et al, ; Ruvalcaba‐Delgadillo et al, ), restraint stress (Barros, Duhalde‐Vega, Caltana, Brusco, & Antonelli, ; García‐Cáceres et al, ), and limited nesting and bedding material during development (Gunn et al, ). Notably, all these models have been described to have effect on astrocytes.…”
Section: Ela Induced Alterations In Astrocytesmentioning
confidence: 93%
“…In development, there is debate as to when the BBB "closes" or begins to regulate the flow of macromolecules into and out of the brain parenchyma. Our previous results suggested that perinatal GABAergic [95] or GC [118] treatments influence BBB development. Evidence currently exists for both sex-dependent GC [119] and reproductive hormone [120] influences on some aspects of BBB function, such as permeability and expression of molecular pumps.…”
Section: Anatomy Of Stress and Role Of Paraventricular Nucleusmentioning
confidence: 93%